Análise emergética da produção de frangos de corte em aviário dark house - Nolasco, Kariny Carvalho Vieira (2022)
The energy analysis, from its indicators, has shown to be an interesting method to contribute to the evaluation of the sustainability of an agricultural biosystem, by determining the energy contained in different sources of biomass, its products and by-products. However, the emergetic synthesis has been considered as a more accurate form of analysis, by providing an integral and systemic assessment of sustainability, since it allows the verification, in a strategic way, of the positive and negative aspects involved in the production process of a particular product or service, because it is the sum of the total energy. In this context, considering the importance of identifying the limitations of a poultry housing system and contributing to the identification of more sustainable methods and materials, this study aimed to perform an emergenthic analysis of the production of broilers, raised in a Dark House typology system. The emergetic analysis performed in this study followed three methodological steps: 1) elaboration of the systemic diagram from the observation and understanding of energy and matter flows acting in each production system, based on symbolic language; 2) assembly of tables to calculate the total emergy of the systems and obtaining the emergetic indicators of the systems under study; 3) interpretation and discussion of the values obtained in the emergetic indicators. The emergetic indicators presented as the yield rate (EYR), investment rate (EIR), environmental load (ERL) and the sustainability index (ESI), allowed to have a broader view of the system efficiency, having been found the need for improvements for its better performance. According to the results obtained, without adjustments in the system studied, there is an indication that it may not contribute to economic growth and also may not be sustainable.